2019
DOI: 10.3201/eid2503.180297
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Selection of a Unique Tandem Repeat Mediated Azole Resistance Mechanism (TR120) inAspergillus fumigatus cyp51A, Denmark

Abstract: We report a fatal aspergillosis case in which STR Af typing and whole-genome sequencing substantiated in vivo emergence of an azole-resistant Aspergillus fumigatus with a 120-bp tandem repeat in the promoter region of cyp51A . This event, previously restricted to the environment, challenges current understanding of azole resistance development in A. fumigatus .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 15 publications
3
45
0
Order By: Relevance
“…Furthermore, the TR 34 /L98H strain was discovered in a sample mixed with the TR 34 3 /L98H strain and had a white and slow-growing phenotype, which could help explain why it could potentially have been overlooked in earlier samples. Indeed, the in vivo acquisition of a tandem repeat in the promotor region has been reported from our group, where a 120-basepair tandem repeat evolved in a patient during azole therapy, supported by whole-genome sequencing (WGS) (Hare et al, 2019). It has also been suggested that the TR 34 helps compensate for loss of fitness associated with the L98H change (Verweij et al, 2016) and thus the additional TR 34 could potentially further improve fitness and outgrow the TR 34 /L98H, which in this patient appeared with a weaker phenotype (Verweij et al, 2016).…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, the TR 34 /L98H strain was discovered in a sample mixed with the TR 34 3 /L98H strain and had a white and slow-growing phenotype, which could help explain why it could potentially have been overlooked in earlier samples. Indeed, the in vivo acquisition of a tandem repeat in the promotor region has been reported from our group, where a 120-basepair tandem repeat evolved in a patient during azole therapy, supported by whole-genome sequencing (WGS) (Hare et al, 2019). It has also been suggested that the TR 34 helps compensate for loss of fitness associated with the L98H change (Verweij et al, 2016) and thus the additional TR 34 could potentially further improve fitness and outgrow the TR 34 /L98H, which in this patient appeared with a weaker phenotype (Verweij et al, 2016).…”
Section: Discussionmentioning
confidence: 95%
“…Since environmental isolates harboring TR resistance mechanisms are identified in azole-naïve patients on five continents, and the same resistance mechanism was identified in environmental isolates treated with MDIs that share a higher genetic similarity with wild-type isolates, this strongly suggests that clinically acquired azole-resistant isolates are primarily acquired from the environment [4]. A recent study, however, through the use of whole-genome sequencing identified that azole-resistant A. fumigatus isolates harboring TR can also develop during the course of antifungal treatment, which shows the same genotype as the initial azole-susceptible A. fumigatus isolates [240]. It seems that the emergence of azole-resistant fungus in the clinic with the environmental source is not exclusive to molds.…”
Section: Role Of Agriculture In the Development Of Resistancementioning
confidence: 99%
“…Exceptions to the categorization in resistance development routes were recently described as isolates with cyp51A point mutations that have been recovered from the environment and azole-naive patients [17]. In addition, an isolate harboring a tandem repeat in the promotor region (TR120) was shown to have developed in-host through azole therapy [17,18].…”
Section: Aspergillus Resistancementioning
confidence: 99%